Consent for the Pelvic Examination Under Anesthesia by Medical Students: Recommendations by the Association of Professors of Gynecology and Obstetrics. Issue 6 (December 2019) - Hammoud, Maya M.; Spector-Bagdady, Kayte; O'Reilly, Meg; Major, Carol; Baecher-Lind, Laura
Abstract : The pelvic examination is a critical tool for the diagnosis of women's health conditions and remains an important skill necessary for students to master before becoming physicians. Recently, concerns regarding student involvement in pelvic examinations—specifically those performed while a woman is under anesthesia—have been raised in the scientific, professional, and lay literature. These concerns have led to calls to limit or halt the performance of pelvic examinations by students while a woman is under anesthesia. Although ensuring adequate informed consent for teaching pelvic examinations is a priority, we must not lose sight of the critical pedagogical value of teaching pelvic examination in familiarizing students with the female anatomy and instilling a physician workforce with confidence in pelvic examination skills. A compromise that addresses all of these values is possible. In this commentary, we review the educational and legal aspects of the pelvic examination under anesthesia, then provide strategies that individuals and institutions can consider to optimize processes regarding consent for pelvic examination under anesthesia. Abstract : Institutions should develop, implement, and monitor processes to ensure transparency and appropriate consent from patients for medical students performing pelvic examinations under anesthesia.